Examining changes of adolescent physical habitus—a retrospective study of physical capital networks - Bian, Junyi; Xiang, Zubing; Xiang, Xuechun (Frontiers in Psychology, 2024)
In recent years, massive studies have examined sport from the standpoint of cultural capital. However, these studies have not examined cultural capital in relation to habitus within specific fields. This article demonstrates a multivariate latent growth curve model for analyzing changes of participants' physical habitus. Hypotheses concerning the form of growth in physical habitus, individual perceived capital influence differences in the common trajectory over time, and covariates influencing growth of PH were tested. Significant linear increases existed for perceived influence from family and school, while significant linear decreases existed for perceived influence from community. Second-order alternative format of latent growth curve model indicated that associations among individual perceived influence difference could be adequately explained by a higher order physical habitus construct. Gender, personal health condition, family socio-economic status, and weekly time spent on physical activities significantly predicted initial levels of physical habitus, whereas family social economic status significantly predicted the rate of change in physical habitus simultaneously. These findings not only support participation in sport is constructed socially, but also that individual efforts and contextual influences contribute to physical habitus. Furthermore, three types of perceived influences intertwined so much in simultaneity, instead of contributing to physical habitus across time.